Mobility Barriers and Enablers and Their Implications for the Wellbeing of Disabled Children and Young People in Aotearoa New Zealand: A Cross-Sectional Qualitative Study - Smith, M; Calder-Dawe, O; Carroll, P; Kayes, NM; Kearns, R; Lin, E-Y (Judy); Witten, K (Elsevier BV, 2021)
Active participation in community and cultural life is a basic right of all children and young people (CYP) and is central to wellbeing. For disabled CYP, mobility can be constrained through a range of environmental and social/attitudinal barriers. The aim of this research was to understand the enablers and barriers to mobility from the perspectives of disabled CYP. Thirty-five disabled CYP aged between 12 and 25 years took part. Data were collected in Tāmaki Makaurau Auckland, Aotearoa New Zealand from mid-2016 to early 2018. Face-to-face interviews and go-along interviews were conducted and were transcribed verbatim. An iterative, thematic approach to analysis was undertaken. Mobility played an essential role in enabling wellbeing, connecting CYP to people, places and possibilities. While the possible impediments to smooth transit appeared infinite, numerous examples of overcoming barriers to mobility were evidenced across a range of factors. Dis/ableism was a pervasive barrier to mobility. The rights to access and experience the city for young people in this study were compromised by transport networks and social norms as well as values that privilege the movement of non-disabled bodies. The findings demonstrate that reducing ableist presumptions about preferences and abilities of disabled CYP, alongside ensuring practical enablers across the transport system must be key priorities for enhancing the wellbeing of this group.